1994
DOI: 10.1088/0953-4075/27/6/018
|View full text |Cite
|
Sign up to set email alerts
|

The current status of superelastic scattering studies for e--Na atom collisions

Abstract: New data from a superelastic scattering experiment on e--Na atom collisions at 10, 15, 20, 25 and 30 eV incident energy are presented and compared with existing experimental data and theories based respectively on the distorted wave second-order Born approximation, 15 state close-coupling and coupled channel optical potential calculations. Overall, fair to good agreement is found between theory and experiments for individual atomic scattering parameters. The loss of coherence previously observed by some worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Computer Stokes parameters for (i) the excitation of the 3S-3P transition and (ii) the de-excitation of the 4S-3P transition by 22 eV incident electrons. Previous measurements by Scholten et al (1993), Sang et al (1994) and Hermann et al (1977) are shown together with the present data and calculations.…”
Section: Methodssupporting
confidence: 66%
“…Computer Stokes parameters for (i) the excitation of the 3S-3P transition and (ii) the de-excitation of the 4S-3P transition by 22 eV incident electrons. Previous measurements by Scholten et al (1993), Sang et al (1994) and Hermann et al (1977) are shown together with the present data and calculations.…”
Section: Methodssupporting
confidence: 66%
“…Rabi frequency (GHz) Measurements involving electron superelastic scattering from the 32P3/2 level of Na excited from both states of the 3 2 S1/ 2 ground level by radiation from two lasers have been performed recently (Sang et al 1994). Values for pi and P~ at electron scattering angles of greater than 15° were able to be obtained.…”
Section: Superelastic Scattering Methods (2a) Modelling Of Optical Pummentioning
confidence: 99%
“…The experimental protocol was similar to the single step superelastic scattering experiments (see, for example, Sang et al 1994) and details are given elsewhere (Sang 1995). The energy gaps between the 3 2 S1/ 2 and the 3 2 P 3 / 2 levels and the 3 2 P 3 / 2 and 32D5/2 levels are 2·1 and 1· 6 e V respectively.…”
Section: (2b) Electron Superelastic Scattering From the 3 2 D S / 2 Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Shortly thereafter similar studies on Ba (see, e.g., Register et al 1978Register et al , 1983 were initiated in our laboratory. Measurements have been reported subsequently on Na (Herman and Hertel 1982, McClelland et al 1992, Sang et al 1994, Hall et al 1996, Ba (Zetner et al 1990, Li and Zetner 1994a, Ca Teubner 1995, Teubner et al 1996), Li (Karagonov et al 1996, Rb (Hall et al 1996), Cr (Hanne et al 1993) and Yb (Li and Zetner 1994b). In these studies the superelastic scattering signal corresponding to the electron-impact de-excitation of the laser-prepared state to the ground state was measured as a function of the laser geometry and polarization (with respect to the collision frame).…”
Section: Introductionmentioning
confidence: 98%